2015
DOI: 10.1007/s10735-015-9631-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of FGF-2, -7, -8, -10 and FGFR-1–4 during regeneration of the rat submandibular gland

Abstract: Fibroblast growth factors (FGFs) and their receptors (FGFRs) play important roles in the development of the submandibular gland. Although regeneration of submandibular glands follows a similar process to their development, it is unknown how FGFs and FGFRs are distributed during regeneration of submandibular gland. The aim of this study was to determine the localization of FGFs and FGFRs during such regenerative processes. After 7 days' obstruction, the submandibular glands were collected at days 0, 1, 3, 7, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Previous studies of the obstruction and release of obstruction of salivary glands have been conducted over approximately 1 week [23, 27, 28]. We chose to examine changes in glandular tissue structure, residual function and regenerative capacity after the release of submandibular gland obstruction in conditions that more closely mimic those encountered in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the obstruction and release of obstruction of salivary glands have been conducted over approximately 1 week [23, 27, 28]. We chose to examine changes in glandular tissue structure, residual function and regenerative capacity after the release of submandibular gland obstruction in conditions that more closely mimic those encountered in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-2/FGF receptor-1 signaling was found to promote atrophic rat submandibular gland repair [17]. There is a report of localization of FGFs and FGF receptors during atrophic rat submandibular gland regeneration [16], and it has been suggested that epidermal growth factor affects atrophy regeneration [14,15]. However, the process of identifying the function of these growth factors is one of atrophy/regeneration, and no study has evaluated the effect on the necrotic region.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies of atrophy and regeneration of salivary glands in the above experimental systems revealed localization of growth factors such as epidermal growth factor [14,15], fibroblast growth factors (FGFs) [16], and nerve growth factor [14]. However, their roles remain unclear, and the long-term effects of procedures such as intra-ductal retrograde injection of growth factors are unknown [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies examining novel therapeutic approaches that aim to regenerate the salivary glands and maintain normal salivary secretion are essential for affected patients. Currently, there are three main strategies for restoring salivary gland function: i) The insertion of a therapeutic gene into ductal cells or residual salivary gland acinar cells by retrograde injection of lentivirus as a vector ( 12 ); ii) the activation of stem cell proliferation or differentiation in the gland ( 13 ); and iii) the elucidation of signaling pathways associated with salivary gland regeneration ( 12 ). Among these three approaches, gene therapy allows for the identification of key genes responsible for regulating the regeneration and repair of duct calculus-induced salivary gland fibrosis ( 14 ).…”
Section: Introductionmentioning
confidence: 99%